Website Security Analysis Using Penetration Testing - Utama, Anugrah; Khairil, Khairil; Supardi, Reno (oneamrd (One a Mllions Dreams Corporation), 2025)
Websites are a vital element in the evolution of the internet, with more than 1.9 billion sites worldwide today. Their use was initially limited to personal purposes, but now almost every company has a website, such as Facebook, Apple, and BBC News. Tim Berners-Lee created the first website in the late 1980s through the World Wide Web (W3) project. Penetration Testing is an evaluation method to identify weaknesses in the security of a system, network, or web application. It involves a direct attack on the target being tested to detect and fix weaknesses. The goal is to identify potential weak points and ensure compliance with security policies. The test results using Accuntetix showed a low-level system vulnerability on the min2kotabengkulu.sch.id website, which can be considered quite safe from attacks